Plasminogen influence on the PAI-1 release by human platelets - O. I. Yusova; T. V. Grinenko; T. F. Drobot’ko; A. O. Tykhomyrov (The Ukrainian Biochemical Journal, 2024)
РАІ-1 (plasminogen activator inhibitor type 1), as a major physiological inhibitor of tissue plasminogen activator and urokinase, plays a key role in the regulation of fibrinolysis in vivo. Besides, PAI-1 suppresses plasmin formation and affects cell migration through interaction with vitronectin. РАІ-1 is secreted from α-granules of platelets upon stimulation of cells by agonists. The aim of our study was to explore the effects of Glu- and Lys-forms of plasminogen on PAI-1 secretion by platelets and to evaluate the possible role of plasminogen in modulation of agonist-induced PAI-1 release. The secretion of PAI-1 by platelets was investigated by the Western blot analysis. It has been established that depending on the agonist, PAI-1 can be released from platelets in a free form, in a complex with a tissue plasminogen activator, as well as in the form of high-molecular complexes that contain a tissue activator and vitronectin molecules. The revealed induction of PAI-1 secretion under the action of Gly- and Lys-forms of plasminogen indicates their ability to activate intracellular signaling pathways that regulate the release of platelet α-granules. Our findings may be of importance for elucidating the pathogenetic mechanisms of many diseases associated with abnormally enhanced platelet function and PAI-1-related disorders.